Pengaruh Terapi Rekreasi terhadap Fungsi Kognitif Kelompok Lansia di Masyarakat - Devi, Hilda Mazarina; Putri, Ronasari Mahaji (Jurnal Akademika Baiturrahim Jambi, 2024)
The decline in cognitive abilities is often viewed as a normal issue and is considered a natural occurrence in old age. This decline is characterized by frequent forgetfulness, which is one of the early symptoms of senility among the elderly. To date, no research has been conducted on the effectiveness of recreational therapy, specifically brain gym exercises and memory games made from recycled materials, on the cognitive functions of the elderly residing in RT 06 RW 01 Tanjungrejo, Sukun, Malang City. This study aims to examine the relationship and impact of recreational therapy on the cognitive function of the elderly. It employs a pre-experimental research design with pretest and post-test assessments. The research population consists of 26 elderly individuals, and total sampling was used to select the samples. Brain gym sessions were conducted 12 times between June and July 2023. The instruments utilized include Mini Mental State Examination questions (11) and an observation sheet to document the implementation of recreational therapy. Data analysis was performed using the marginal homogeneity test. The results indicate a significant relationship between recreational therapy, involving brain gym exercises and memory games made from recycled materials, and the cognitive function of the elderly (p-value = .025 < .050). Based on these findings, it is recommended to motivate the elderly to continue participating in recreational therapy to prevent further decline in cognitive function. Moreover, recreational therapy can be promoted as a beneficial activity for the elderly, enhancing social interaction with their families